Clinical Outcomes of Unprotected Left Main Stem Stenting: An Observational Single-Centre Study - Muhammad Abdur Rauf, Jehandad Khan, Samiullah, Syed Tahir Shah, Imad Uddin, Sarmad Raza, Mehmood Ul Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To know the clinical outcomes of percutaneous intervention (PCI) with drug eluting stents (DES) in patients with unprotected left main stem disease. Materials and Methods: This single-centre, prospective, observational study was conducted on 133 patients, who underwent PCI using DES to an unprotected LMS at Kuwait teaching Hospital Peshawar, between 2018 to 2022. Patients were followed in OPD and clinics or they were traced through calls at monthly and yearly intervals, after the procedure. A team, which comprised of a cardiac interventionist and a cardiac surgeon, scrutinised patients for the eligibility of either procedure. Ethical Committee approval was granted by the Institutional Ethics committee. Results: At 1month follow up, the composite end point occurred in 13 (11.58%) patients, whereas individual secondary end points including death from all-cause mortality was reported in 5 (4.7%), stroke in 1 (0.9 %), MI in 4 (3.73 %) and repeat vascularisation in 3 (2.25%) patients. The annual incidence of composite end point occurred in 27.58%patients, whereas individual secondary end points including death from all-cause mortality was reported in 10 (8.27%), stroke in 3 (2.25 %), MI in 09 (6.76%) and repeat vascularisation in 11 (10.3%) patients, Conclusion: PCI to LMS can be performed safely in centres having no cardiac surgery backup and newer imaging modalities with results comparable to the centres having the luxury of such facilities, provided that operators are skilled enough with sufficient expertise and knowledge.